Fungal sensitization in childhood persistent asthma is associated with disease severity. Issue 1 (8th February 2013) - Vicencio, Alfin G.; Santiago, Maria Teresa; Tsirilakis, Kalliope; Stone, Anne; Worgall, Stefan; Foley, Elizabeth A.; Bush, Douglas; Goldman, David L.
Abstract Rationale Recent observations, especially in adults, suggest that asthma severity may be associated with fungal sensitization. Other studies suggest that some patients with severe asthma and fungal sensitization may benefit from anti‐fungal therapy. Currently, the prevalence of fungal sensitization among children with severe asthma is not well characterized. Methods We determined prevalence of fungal sensitization among children with moderate to severe persistent asthma and compared clinical characteristics between sensitized and non‐sensitized children, including asthma severity, serum immunoglobulin E, and pulmonary function. Results Of the 64 children enrolled, 25 (39%) had evidence of sensitization to one or more fungi. Nineteen of 25 (76%) children with fungal sensitization were categorized as severe persistent compared to 13 of 39 (33%) children without evidence of fungal sensitization (odds ratio = 6.33, 95% confidence interval 2.04–19.68, P = 0.0014). Of 32 severe persistent asthmatics, 19 (59%) demonstrated evidence of fungal sensitization. Serum immunoglobulin E was significantly higher (P < 0.001), and pulmonary function (including FEV1, FEV1/FVC, and FEF25–75%) significantly lower in the fungal‐sensitized patients (P = 0.016, 0.0004, and 0.002, respectively). Bronchial biopsy of sensitized children revealed basement membrane thickening and eosinophil infiltration. Conclusions Fungal sensitization in children with persistent asthma is associated with disease severity. Almost 60% of our severe persistent asthma patients had evidence of fungal sensitization and, based on our previous studies, may be potential candidates for anti‐fungal therapy. Pediatr Pulmonol. 2014; 49:8–14. © 2013 Wiley Periodicals, Inc.